Impact of tunable oligophosphonates on barium sulfate crystallization - Ogden, Mark; Raston, C.; Radomirovic, Tomoko; Jones, Franca (American Chemical Society, 2014)
Calixarenes can be used as well-defined scaffolds for investigating structure–activity relationships of additives and their impact on crystallization. In this work, we present the crystal growth modification of barium sulfate by p-phosphonic acid calix[n]arenes that vary in size (n = 4, 5, 6, and 8) and thus vary in the size of the internal cavity for the same functionality in the upper rim. The tetrameric, hexameric, and octameric macrocycles induce nanoparticle formation with clear superstructure. In the case of the hexameric calix[6]arene, the initial mesocrystalline superstructure fuses over time to form almost hollow spheres, while the mesocrystals formed in the presence of the tetramer and octamer are stable over an extended period. The pentameric calix[5]arene forms more disordered aggregates of single crystals. Thermogravimetric data shows that a significant proportion of the mass of the barium sulfate-containing solid is the macrocycle, regardless of the choice of macrocycle.